The exploration of accountability frameworks for sewage works management at the City of Mbombela LocalMunicipality - Selepe, Mamaropeng Marcus (University of the Witwatersrand, Johannesburg, 2024)
This study used the City of Mbombela Local Municipality as a case study to investigate how accountability mechanisms are implemented for wastewater treatment works. Wastewater treatment works generally perform poorly and discharge poor quality effluent into our water resources causing pollution and possible health effects. The City of Mbombela Local Municipality own eight wastewater treatment works. The Green Drop progress report for 2023 showed that five of the wastewater treatment works which are managed by the municipality perform poorly compared to the three which are manged by the municipal water services provider, Silulumanzi. The purpose of the study was to determine what accountability challenges are experienced by those assigned the function of managing wastewater treatment works at the City of Mbombela Local Municipality. The study adopted a qualitative research approach and collected data through semi-structured interviews. The results of this study show that the City of Mbombela Local Municipality does not have formal accountability mechanisms in place to hold those assigned the responsibility of managing wastewater treatment works accountable for the performance thereof. This study has revealed the absence of accountability as a possible contributor to the resultant poor performance of wastewater treatment at the City of Mbombela Local Municipality. The findings of the study could inform practice and offer insights about practices in the wastewater management business. It is recommended that municipal managers include the performance of wastewater treatment works as a performance indicator in their annual performance plans as well as in performance agreements of officials responsible for the management of wastewater treatment works. This will enable municipal managers to have a handle on the performance and compliance of wastewater treatment works as these will be reported at the required frequency and subjected to appropriate scrutiny. It is further recommended that a follow up study be conducted to compare accountability mechanisms for wastewater treatment works managed by municipalities against those managed by independent water service providers.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Accountability; Compliance; Performance; Responsibility; Target; Sanction; Sewage Works; Waste Water Treatment Works; SDG-17: Partnerships for the goals